Impact of the new national health standard for rail safety workers on ischaemic heart disease risk factors in train drivers. Issue 6 (9th June 2013) - Ng, K. L.; Quinn, S.; Gill, T. K.; Hill, C.; Shanahan, E. M.
Abstract Background In 2004, a compulsory National Standard for the Australian rail industry was introduced outlining health standards that drivers must meet to be deemed fit to drive. Aim To examine the trend in ischaemic heart disease (IHD) risk factors in train drivers between 2004 and 2009, following the introduction of a National Standard. Methods A retrospective analysis of IHD risk factors of drivers (n = 386) of an Australian train company, who underwent health assessments between February 2004 and November 2009, was performed. The Framingham Score for 10‐year risk of coronary artery disease, body mass index (BMI), cigarette smoking, diabetes, systolic and diastolic blood pressure, high‐density lipoprotein (HDL), low‐density lipoprotein and total cholesterol were compared with that of controls at these two time periods. Results There were significant reductions in the rates of 10‐year coronary heart disease risk/year (OR = 0.47; 95% CI 0.19, 0.75) in the train drivers compared with the control population. This was driven by a reduction in the rate of cigarette smoking (OR = 0.87; 95% CI 0.79, 0.96) and total cholesterol (OR = −0.05; 95% CI −0.09, 0.003) and an increase in HDL cholesterol levels (OR = 0.02; 95% CI 0.006, 0.03) between groups over time. This was despite an increase in BMI (OR = 0.10; 95% CI 0.01, 0.19). Conclusion Following the introduction of a National Standard for drivers in Australia, there has been a significant improvement in the health of drivers. Such a programme may have a significant impact in this group of safety critical workers.